Analisis Minat Penggunaan Mobile Banking Dengan Pendekatan Technology Acceptance Model (TAM) Yang Telah Dimodifikasi - Hanif Astika Kurniawati; Alfi Arif; Wahyu Agus Winarno (UPT Penerbitan Universitas Jember, 2017)
This study aimed to analyze the factors that may affect students' perceptions about the intention to use mobile bankingapplications to support their daily activities. The research model was developed using a Technology Acceptance Modeldeveloped by Davis (1989), and by including three external variables that experience, complexity, and gander. The researchmodel empirically tested using data from a survey of students at the University of Jember. The sampling method in this studyusing a clustered random sampling. The questionnaire of 120 students who receive offers mobile banking service that qualifiesas a sample analyzed using Structural Equation Modelling (SEM) using AMOS 22.0. The results showed that all constructs inthe original TAM model was statistically significant. On the other hand, gender as external variables in this study had no effecton perceived usefulness and perceived ease of use. The implications of this study are relevant for students who are interested inusing mobile banking in order to better take into account the experience and ease of use. Mobile banking users is expected tobe more confident with using mobile banking can simplify their banking activity.